Extraction Methods and Bioactivity of Essential Oils from Kesum Leaves (Persicaria odorata): A Short Review - Utoro, Panggulu Ahmad Ramadhani; Witoyo, Jatmiko Eko; Alvianto, Dikianur; Permatasari, Nelsy Dian (Program Studi Pendidikan Biologi, FKIP, Universitas Nusa Nipa, 2022)
Persicaria odorata (Synonym of Polygonatum odoratum and Polygonum minus) leaves, locally known as Kesum leaves, is one of Indonesia's biodiversity species, particularly on Kalimantan Island, and it is contained a high concentration of essential oils. The extraction of essential oil from Kesum leaves commonly uses various methods, including solvent extraction, steam distillation, hydro-distillation, supercritical fluid extraction, microwave-assisted extraction, ultrasonic-assisted extraction, and so on, with various extract characteristics produced. Several studies reported that Kesum leaves essential oil has numerous advantages, including anti-bacterial, hepatoprotective, anti-tyrosinase, antioxidant properties, and so on. Future research will require additional and new techniques, particularly non-thermal extraction technology and other bioactivity tests, to improve yield and maintain the essential oil composition of Kesum leaves.Â